Estudo de padrões funcionais de comunidades campestres sob fertilização e manejo pastoril no Alto Camaquã, RS - Moterle, Alessandro Freire (2013)
The impact arising from livestock activity in grassland ecosystems reflects a long history of how this activity was carried. One alternative of lasting management for conservation of these lands is to use the capacity of resilience of natural grassland, in which important tools for recovery are control of leaf defoliation and nutrient replacement. Changes in vegetation take place throughout time and space by a broad range of factors and, for their interpretation, plant s mechanisms of capture and storage of resources must be understood. Plant functional types are one approach highlighted at large scale responses. However to make this framework operational, it depends on knowledge of species development and especially their role in biomass production or in ecological processes at the landscape level. This work s hypothesis is that communities ranked into functional groups of plants may show patterns of biomass distribution along the community that are related to environmental factors and management. The experiment was conducted in livestock farms (UEPAs) enrolled in a project linked to EMBRAPA-CPPSUL established since 2008. In such UEPAs rotational grazing and natural fertilizers were applied together in natural grassland paddocks. Four surveys were conducted for assessment of species contribution on biomass since April/2012 to September/2011. Poaceae species were ranked according to its contribution in vegetation, through their morphological traits: specific leaf area and leaf dry matter content. This approach allows defining groups of species with different features even for large-scale environmental factors . Through biomass accumulation of plant groups with similar functional traits it was possible to diagnose vegetation patterns in response to environmental and management factors.